ONLINE GAME TO IMPROVE ENGLISH VOCABULARY: A BIBLIOMETRIC ANALYSIS - Fastabiqul Khairati (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to evaluate and analyse the research that has been conducted on the use of online games to improve English vocabulary. This research uses bibliometric analysis method to analyse and evaluate articles, journals, and conference papers related to Online Game To Improve English Vocabulary. This study collected metadata from Google Scholar through publish or perish in the last 7 years (2017-2023) and visualised with VOSviewer, then analysed and evaluated based on country, author bibliographic pairs, and co-occurrence of author keywords. A total of 463 publications were selected following the research criteria in the last 7 years (2017-2023). The results show that Indonesia is the country where there is a very rapid increase in this research. Hashim, harmawati (Indonesia) (based on author's bibliography ) in this study. Language learning, Games and English Vocabulary became the most influential keywords in this study. The results show that there has been a significant increase in research conducted on the use of online games to improve English vocabulary over the past few years. In addition, the analysis identified trends and patterns in this research, including the use of online games as an effective tool for improving English vocabulary, particularly among students. This research suggests that online games can be a useful tool for improving English vocabulary and can help in developing better strategies and practices for teaching English.